HUBUNGAN DUKUNGAN KELUARGA DENGAN PARENTING SELF EFFICACY PADA IBU POSTPARTUM DI KABUPATEN BANTUL - Yanita Trisetiyaningsih; Dwi Susanti (Universitas Respati Yogyakarta, 2021)
The Corelation Between Family Support with Parenting Self Efficacy In Postpartum Mother In Bantul RegencyBackground: the postpartum a period of crisis for a mother husband and family so arious changes physically, psychologically and family structure. The process is related to parenting self-efficacy. Parenting self-efficacy is self-confidence and the mother’s ability to caring the baby. Several factors influence the mother’s parenting self-efficacy in caring for her baby, one of which is family support. Objective: this study aims to determine the relationship between family support and parenting self-efficacy of postpartum mothers in Bantul Regency. Methods: this study is a correlation quantitative analytic study with a cross sectional approach with a total sample of 46 respondents taken by accidental sampling technique. Data analyze using Kendall Tau test. Results: most (63%) families support postpartum mothers and most (76,1 %) Postpartum mothers have parenting self-efficacy in the sufficient category. The Kendall Tau result showed a P-value of 0,478. Conclusion: there no relationship between family support and parenting self-efficacy in postpartum mothers in Bantul Regency.